2014
DOI: 10.1111/rda.12324
|View full text |Cite
|
Sign up to set email alerts
|

Use of Antimicrobials in the Treatment of Reproductive Diseases in Cattle and Horses

Abstract: Use of antimicrobials for veterinary indications related to reproduction in cattle and horses is reviewed. Antimicrobial compounds are widely used to treat and prevent infections of reproductive organs. Total amounts of antimicrobials for such purposes, estimated by weight, are low compared with major uses in food animals. The most common reproduction-related indication in cattle is mastitis. The number of intramammary products available for treatment of mastitis in the European Union is high. Metritis and end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 104 publications
(229 reference statements)
0
27
0
3
Order By: Relevance
“…Additionally, only the S. aureus isolates were resistant to penicillin, ampicillin, and intermediate levels of erythromycin. This finding is not surprising as these antimicrobials are commonly used to treat mastitis (Pyörälä et al, 2014) and thus may contribute for the selection of these resistant strains. Even though, in this work, the mecA gene was not detected in any of the strains, using the protocol of Santos et al, (1999); methicillinresistant staphylococci have already been reported as bovine mastitis agents (Seixas et al, 2014) and attention should be paid to monitor the presence of this antimicrobial resistance gene.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Additionally, only the S. aureus isolates were resistant to penicillin, ampicillin, and intermediate levels of erythromycin. This finding is not surprising as these antimicrobials are commonly used to treat mastitis (Pyörälä et al, 2014) and thus may contribute for the selection of these resistant strains. Even though, in this work, the mecA gene was not detected in any of the strains, using the protocol of Santos et al, (1999); methicillinresistant staphylococci have already been reported as bovine mastitis agents (Seixas et al, 2014) and attention should be paid to monitor the presence of this antimicrobial resistance gene.…”
Section: Resultsmentioning
confidence: 82%
“…The disease is classified as moderate or severe, and might be caused by different bacterial species, but mainly Staphyococcus strains (Pyörälä and Taponen, 2009 Coagulase-negative staphylococci (CNS) have been considered pathogens of lesser importance, while Staphylococcus aureus has been considered a more important pathogen due its ability to form biofilm (Lee et al, 2014). However, more recent studies have shown that CNS are emerging pathogens associated with the occurrence of mastitis and persistence of intramammary infection in dairy cattle (Fry et al, 2014).…”
Section: mentioning
confidence: 99%
“…More antibiotics are available for systemic use, but the pharmacokinetic properties are not always suited for uterine infections. In general, high lipid solubility, low protein binding and a high degree of nonionization favor distribution throughout the body (Pyörälä et al 2014).…”
Section: Antimicrobialsmentioning
confidence: 99%
“…Tetracyclines have moderate lipidsolubility and can yield therapeutic concentrations in reproductive organs. However, because of their side-effects tetracyclines are not commonly used in horses (Pyörälä et al 2014). In a Swedish study, enrofloxacin was the only of 10 tested antibiotics for which no E. coli isolate was resistant but 15 % of E. coli isolates were resistant to trimethoprim/sulphamethoxazole, 22 % to streptomycin, 11% to ampicillin and 4 % to gentamicin (Albihn et al 2003).…”
Section: Antimicrobialsmentioning
confidence: 99%
See 1 more Smart Citation